Seismic energy dissipation capacity of confined concrete columns with infilled-AAC bricks subjected to quasi-static cyclic loading - Bambang Sabariman; Tavio; Slamet Widodo (Sustainable Structures)
Autoclaved Aerated Concrete (AAC) is still designated as a non-engineering material because it is considered not to contribute to the stiffness and strength of structural members and is considered limited to infilling material within structural building frames. This provision needs to be reviewed because based on several studies its contribution to the stiffness and strength of the building structure is quite significant. This study involved tests of confined concrete column specimens infilled with AAC. The results indicate that its capability to dissipate the earthquake energy still satisfies all three criteria of the ACI 374.1-05 provisions, such as capability to carry loads > 0.75Ph-max, relative energy dissipation ratio (β) > 0.125, and gradient hysteresis loop limited by drift ratio limit (-0.35% and +0.35) > 0.05. Apart from that, it is also able to enhance the column ductility to reach up to 9.285 (greater than 4), which is categorized as high ductility criteria in FEMA 356. All test columns in the study failed in flexural modes as designed (no shear failures occurred).